Application of The User Centered Design Method To Evaluate The Relationship Between User Experience, User Interface and Customer Satisfaction on Banking Mobile Application - Sudirjo, Frans; Ratna Tungga Dewa, Dominica Maria; Indra Kesuma, Lucky; Suryaningsih, Lilik; Yuniarti Utami, Eva (Jurnal Informasi dan Teknologi, 2024)
The aim of this research is to evaluate user satisfaction through UI/UX design in mobile banking and find out what kind of UI/UX appearance users want using the user-centered design method. This research uses a qualitative approach. In addition to the qualitative approach, this research also incorporates a quantitative approach. Data collection in this research used usability testing, interviews, and questionnaires. We calculated the data obtained from the questionnaire statistically using Microsoft Excel. The results of questionnaire data analysis can be in the form of graphs or numbers. Researchers create a list of required elements or features to maintain, add, improve, or remove after collecting and analyzing data. Researchers will implement the requirements list by providing prototype design recommendations. The research results showed that 90% of participants successfully completed the 10 task scenarios given during the evaluation of ongoing mobile banking usability testing. Furthermore, during the evaluation of mobile banking prototype recommendations, 99% of participants successfully completed the 10 task scenarios that had been given. The appearance that users want is a more attractive appearance by adding more icons and illustrations, as well as making the appearance more modern. Additional features that users want, namely adding an e-wallet top-up feature, not limiting the account mutations that can be seen, adding a share feature after transfer, adding fingerprint and face ID features in the login section, and adding a copy feature to be able to copy account numbers.